Kepemimpinan Kiai dalam Pengembangan Pendidikan Formal di Pondok Pesantren Full Day Sunan Ampel Banyuwangi - Fanani, Ahmad Aziz (IAI Darussalam, 2020)
The focus in this study are: 1) how the behavior of the Kiai recognizes the situation of the pesantren community, 2) the behavior of the Kiai in providing direction and guidance to the community of the pesantren, 3) the behavior of the Kiai giving the delegation of authority to the pesantren community in developing formal education. Type of phenomenological research. Data collection techniques using observation, interviews, documents, and audiovisual materials. Data analysis tools used interactive models. The results of this study: 1) the process of diagonalizing the Kiai which is carried out in the internal and external environment of the pesantren applies three important components, namely religious compatibility, commitment, and competence, 2) direction and guidance of the Kiai is carried out based on the maturity of the community which is described rationally through Kiai's scatted concept of maturity rate, 3) variable delegation of authority based on the scale of maturity and the development of a hierarchical structure. The conditions develop according to the competency scale, while the initiation is in line with the development of commitment.